Impact of aeration on macrophyte establishment in sub-surface constructed wetlands used for tertiary treatment of sewage - Butterworth, Eleanor; Richards, Andrew; Jones, Mark; Brix, Hans; Dotro, Gabriela; Jefferson, Bruce (Elsevier, 2016)
The effect of artificial aeration on plant growth in constructed wetlands in terms of above and below ground biomass and nutrient uptake of two macrophyte species Phragmites australis and Typha latifolia was carried out to provide quantitative, mechanistic evidence to support any differences between the plant species establishment. Pilot scale systems were built and supplied with different intensities of aeration and corresponding controls, with supporting evidence from two full scale operational sites. Results show T. latifolia was more impacted by aeration than P. australis when comparing against their respective non-aerated controls, evidenced in reduced height, growth rate and leaf length. However, the impact was less visible due to T. latifolia's faster growth rate compared to P. australis. Micro and macronutrient uptake by each species had no discernible pattern, preventing the identification of a definitive mechanism to explain the retarded growth. However, results suggest a synergy between iron and manganese may be at play.
Keywords: Aeration; Plant development; Reed beds; Nutrients; Biomass; Wastewater